The Effect of Etching Time On Structural Properties of Porous Quaternary AlInGaN Thin Films - Tomaa, Ghasaq Ali; Ghazai, Alaa Jabbar (Iraqi Journal of Physics, 2021)
Using photo electrochemical etching technique (PEC), porous silicon (PS) layers were produced on n-type silicon (Si) wafers to generate porous silicon for n-type with an orientation of (111) The results of etching time were investigated at: (5,10,15 min). X-ray diffraction experiments revealed differences between the surface of the sample sheet and the synthesized porous silicon. The largest crystal size is (30 nm) and the lowest crystal size is (28.6 nm) The analysis of Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscope (FESEM) were used to research the morphology of porous silicon layer. As etching time increased, AFM findings showed that root mean square (RMS) of roughness and porous silicon grain size decreased and FESEM showed a homogeneous pattern and verified the formation of uniform porous silicon.